Pengaruh Holistic Comfort Care terhadap Parameter Fisiologis Pasien Neonatus dengan Asfiksia di Ruang NICU: Studi Kasus - Arinandika, Kailifah Nurul; Indarwati, Ferika; Winarni, Winarni (Pustaka Galeri Mandiri, 2025)
Asphyxia is one of the life-threatening emergency conditions for newborns (neonates). Neonates with asphyxia undergo treatment in the Neonatal Intensive Care Unit (NICU) to improve their condition. One of the therapeutic nursing interventions that can be given to neonates is Comfort care. Comfort care can be used as a specific and comprehensive (Holistic) intervention that includes neonates' physical and psychological aspects. The purpose of this study was to determine the effect of holistic comfort care (nesting position, light reduction, white noise, and bounding attachment) on improving physiological parameters and comfort of neonates with asphyxia in the NICU. The method in this study is a case report involving neonatal patients with asphyxia in the NICU. Monitoring was carried out before and after the intervention with instruments consisting of vital signs (heart rate, respiratory rate, SPO2) and the Comfort Neo Scale. The results of the study showed that the implementation of comfort care intervention for 5 days improves physiological parameters in particular pulse rate, breathing rate, oxygen saturation, and comfort in neonates with asphyxia. Based on these results, comfort care can be an alternative to nursing interventions that can improve the outcomes of babies with asphyxia who are treated in the NICU room.